Titanium-steel composite plate macro-etching agent, etching method and device

CN116590710BActive Publication Date: 2026-10-27PANZHIHUA IRON & STEEL RES INST OF PANGANG GROUP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310542995.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-15
Publication Date
2026-10-27
Estimated Expiration
2043-05-15

AI Technical Summary

Technical Problem

[0004]公开号ZL201410100333.1《一种钛钢复合板低倍检验方法》中,腐蚀采用分步腐蚀法,即先采用氢氟酸、硝酸、水溶液擦拭钛侧表面,再采用盐酸水溶液热腐蚀,该方法腐蚀复杂,不易操作

Benefits of technology

1、本发明提供的钛钢复合板低倍腐蚀剂及腐蚀方法和装置,可准确显示钛钢复合板低倍信息,可直接测定钛侧、钢侧尺寸,间接评价钛、钢两侧平直度及复合界面的复合质量,对钛钢复合板的开发应用起到支撑作用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116590710B_ABST
    Figure CN116590710B_ABST
Patent Text Reader

Abstract

The application provides a titanium-steel composite plate low-multiple corrosion agent and a corrosion method and device. The corrosion agent is a mixed solution of potassium fluoride, sulfuric acid, oxalic acid, formic acid, nitric acid, di-o-tolylthiourea, sodium lauryl polyether sulfate and water. The content of potassium fluoride is 1-5 mass parts, the content of sulfuric acid is 10-15 volume parts, the content of oxalic acid is 5-10 mass parts, the content of formic acid is 5-10 mass parts, the content of nitric acid is 3-8 volume parts, the content of di-o-tolylthiourea is 0.5-1 mass part, the content of sodium lauryl polyether sulfate is 0.5-2 mass parts, and the water in the solution is distilled water. The application can accurately show the low-multiple information of the titanium-steel composite plate, can directly measure the sizes of the titanium side and the steel side, and indirectly evaluate the flatness of the titanium side and the steel side and the composite quality of the composite interface, thereby supporting the development and application of the titanium-steel composite plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of physical testing technology for metallic materials, and more particularly to a low-magnification etchant, etching method, and apparatus for titanium-steel composite plates. Background Technology

[0002] The GB / T8547-2006 standard for titanium-steel composite plates requires that the surface of the composite material be free from macroscopic defects such as cracks, peeling, creases, and metallic or non-metallic inclusions. Low-magnification pickling is commonly used as a means of inspecting macroscopic defects. In summary, effectively displaying the low-magnification morphology of titanium-steel composite plates is of great significance for studying the bonding state between the matrix and the cladding, between cladding layers, the quality of the bonding areas on both sides, accurate measurement of cladding thickness, and effective measurement of the bonding area of ​​the cladding layers.

[0003] Chinese patent application CN102072834A discloses a method for observing the metallographic structure of the titanium / steel explosive weld interface. This patent application mainly relates to the high-magnification metallographic corrosion of titanium-steel composite plates and its observation method.

[0004] The publication number ZL201410100333.1, "A Low-Magnification Inspection Method for Titanium-Steel Composite Plates," employs a step-by-step corrosion method. This involves first wiping the titanium side surface with a mixture of hydrofluoric acid, nitric acid, and an aqueous solution, followed by thermal corrosion with a hydrochloric acid aqueous solution. This method is complex and difficult to operate. The method of this invention uses a mixed solution of hydrofluoric acid, hydrochloric acid, and water to achieve one-step corrosion, making the method simple and easy to operate.

[0005] The method of this invention uses an HF-free corrosion method, which can avoid the health damage of HF to operators. Summary of the Invention

[0006] In view of the technical problem of low-magnification microstructure display of titanium-steel composite plates mentioned above, a low-magnification etchant, etching method and apparatus for titanium-steel composite plates are provided.

[0007] The technical means employed in this invention are as follows: A low-magnification etchant for titanium-steel composite plates, wherein the etchant is a mixed solution of potassium fluoride, sulfuric acid, oxalic acid, formic acid, nitric acid, di-o-toluenethiourea, sodium lauryl ether sulfate, and water, wherein the content of potassium fluoride is 1-5 parts by mass, the content of sulfuric acid is 10-15 parts by volume, the content of oxalic acid is 5-10 parts by mass, the content of formic acid is 5-10 parts by mass, the content of nitric acid is 3-8 parts by volume, the content of di-o-toluenethiourea is 0.5-1 parts by mass, the content of sodium lauryl ether sulfate is 0.5-2 parts by mass, and the water in the solution is distilled water.

[0008] Furthermore, the etching temperature of the low-magnification etchant on the titanium-steel composite plate for the low-magnification sample is 30~45℃, and the etching time is 2~8min.

[0009] Furthermore, the titanium-steel composite plate material has a titanium cladding layer and a steel base layer, wherein the titanium is TA1, TA2, TA3, or TA4, and the steel is Q215, Q235, Q255, or Q275.

[0010] This invention also provides a low-magnification corrosion method for titanium-steel composite plates, the method comprising the following steps: S1. Take a section of the TA1 and Q235 titanium steel composite material, process the composite interface into a low-magnification sample, check that the surface roughness of the observation surface has reached the requirement of 3.2μmRa, and clean the entire sample with hot laundry detergent solution to remove oil stains from the surface of the low-magnification sample. S2. Prepare a low-component corrosive agent for titanium-steel composite materials and place the prepared corrosive agent in tank No. 1. S3. Prepare the neutralization solution and place the prepared neutralization solution in tank No. 3; S4. Prepare the cleaning agent and store it separately after preparation. S5. Place the test sample on the sample placement pad, and deliver the corrosive agent to the No. 2 tank through the first liquid inlet system. Start the heating device and the outer cooling system to control the corrosion process within the temperature range of 30℃~45℃. After the test sample is thermally eroded for 5 minutes, return the corrosive agent to the No. 1 tank through the first reflux system. S6. Start the second liquid inlet system to deliver the neutralizing liquid to the second tank. After the test sample is fully neutralized, start the second reflux system to return the neutralizing liquid to the third tank. S7. Add tap water to tank No. 2 to rinse the test sample obtained in step S6. The waste liquid after rinsing enters tank No. 5. S8. Remove the sample and wipe it with a cleaning agent to remove the corrosion deposits on the sample surface. Then rinse and dry the sample. S9. Observe the bonding interface and the surface quality of the titanium and steel layers of the corroded low-magnification sample with the naked eye or stereomicroscope.

[0011] Further, in step S2, the low-magnification corrosive agent for the titanium-steel composite material includes: 2 parts by mass of potassium fluoride, 10 parts by volume of sulfuric acid, 8 parts by mass of oxalic acid, 5 parts by mass of formic acid, 6 parts by volume of nitric acid, 1 part by mass of di-o-toluenethiourea, 1 part by mass of sodium lauryl ether sulfate, and the remainder is water.

[0012] Furthermore, in step S3, the neutralizing solution is a saturated sodium bicarbonate aqueous solution.

[0013] Further, in step S4, the cleaning agent includes: 3-6 parts by volume of nitric acid, 100 parts by volume of ethanol and 1-3 drops of detergent.

[0014] The present invention also provides an apparatus for realizing a low-magnification corrosion method for titanium-steel composite plates, comprising: a No. 1 tank, a No. 2 tank, a No. 3 tank, a No. 4 tank, and a No. 5 tank; The No. 1 tank is a corrosive agent container, with a cover on the top, a first liquid inlet system connected to the upper side, and a first reflux system connected to the lower side. The second tank is a reaction tank. The first liquid inlet system and the first reflux system are both connected to the second tank. The second tank has a second cover on the outer side of its top, and a temperature display is installed on the second cover. The second tank has a temperature sensor on the inner side of its top, and the temperature sensor is connected to the temperature display. The second tank has a laying-out pad at the bottom inside, and a heating device is installed below the laying-out pad. The outer wall of the second tank has an outer layer of cooling material. The No. 3 tank is a saturated sodium bicarbonate neutralization liquid container. It is equipped with a cover on the top, a second liquid inlet system is connected to the upper side, and a second reflux system is connected to the lower side. Both the second liquid inlet system and the second reflux system are connected to the No. 2 tank. The No. 4 tank is a tap water inlet system, which is connected to the outer cooling material to form an outer cooling system. The No. 5 tank is a waste liquid discharge tank, which is connected to the bottom of the No. 2 tank through a waste liquid inlet system.

[0015] Compared with the prior art, the present invention has the following advantages: 1. The low-magnification etchant, etching method, and apparatus for titanium-steel composite plates provided by this invention can accurately display low-magnification information of titanium-steel composite plates, directly measure the dimensions of the titanium and steel sides, and indirectly evaluate the flatness of the titanium and steel sides and the composite quality of the composite interface, thus playing a supporting role in the development and application of titanium-steel composite plates.

[0016] 2. The low-magnification etchant, etching method, and apparatus for titanium-steel composite plates provided by this invention have the advantage that the low-magnification samples etched with this etchant show clearer details.

[0017] 3. The advantages of the low-magnification corrosive agent, corrosion method and apparatus for titanium-steel composite plates provided by the present invention are that the use of this apparatus for corrosion testing is safer and the operation is more standardized.

[0018] In summary, the technical solution of this invention can solve the problem of low-magnification microstructure display of titanium-steel composite plates in the prior art.

[0019] Based on the above reasons, this invention can be widely applied in fields such as physical testing of metallic materials. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 This is a low-magnification morphology diagram of the titanium-steel composite plate of the present invention.

[0022] Figure 2 This is a low-magnification magnified schematic diagram of the titanium-steel composite plate of the present invention.

[0023] Figure 3 This is a schematic diagram of the low-magnification corrosion device of the present invention.

[0024] In the diagram: 1. Tank No. 1; 101. Lid No. 1; 102. First liquid inlet system; 103. First reflux system; 2. Tank No. 2; 201. Lid No. 2; 202. Temperature sensor; 203. Heating device; 204. Outer cooling material; 205. Layout pad; 3. Tank No. 3; 301. Lid No. 3; 302. Second reflux system; 303. Second liquid inlet system; 4. Tank No. 4; 5. Tank No. 5; 501. Waste liquid inlet system. Detailed Implementation

[0025] It should be noted that, unless otherwise specified, the embodiments and features described in the present invention can be combined with each other. The present invention will now be described in detail with reference to the accompanying drawings and embodiments.

[0026] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0027] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0028] Unless otherwise specifically stated, the relative arrangement, numerical expressions, and values ​​of the components and steps described in these embodiments do not limit the scope of the invention. It should also be understood that, for ease of description, the dimensions of the various parts shown in the drawings are not drawn to actual scale. Techniques, methods, and devices known to those skilled in the art may not be discussed in detail. Any specific values ​​in all examples shown and discussed herein should be interpreted as merely exemplary and not as limitations. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters in the following figures denote similar items; therefore, once an item is defined in one figure, it need not be further discussed in subsequent figures.

[0029] This invention primarily addresses the problem of low-magnification microstructure display of titanium-steel composite plates. It provides an etchant and etching method for simultaneously displaying the microstructure on both sides of a titanium-steel composite plate, namely, a low-magnification etchant and etching method for primary etching of titanium-steel composite plates. This invention belongs to the field of physical testing of metallic materials, and particularly relates to the testing of titanium-steel composite plates.

[0030] The applicable material for this invention is titanium for the cladding layer, preferably TA2, and steel for the base layer, preferably Q235.

[0031] The low-magnification corrosion method of this invention uses a corrosive solution (corrosive agent) that is a mixed solution of potassium fluoride, sulfuric acid, oxalic acid, formic acid, nitric acid, di-o-toluenethiourea, sodium lauryl ether sulfate, and water. The solution contains 1-5 parts by weight of potassium fluoride (analytical grade), 10-15 parts by volume of sulfuric acid, 5-10 parts by weight of oxalic acid, 5-10 parts by weight of formic acid, 3-8 parts by volume of nitric acid, 0.5-1 parts by weight of di-o-toluenethiourea, and 0.5-2 parts by weight of sodium lauryl ether sulfate. The water in the solution is distilled water.

[0032] The etching temperature is 30~45℃. Too low a temperature is not conducive to the reaction, while too high a temperature will cause organic acid decomposition and reduced activity of the corrosion inhibitor. The etching time is 2~8 minutes.

[0033] Neutralizing solution: saturated sodium bicarbonate aqueous solution.

[0034] Cleaning agent: 3-6 parts by volume of nitric acid, 100 parts by volume of ethanol, and 1-3 drops of detergent.

[0035] like Figure 3 As shown, the low-magnification corrosion device used in this invention includes tank 1, tank 2, tank 3, tank 4, and tank 5.

[0036] Tank 1 is a corrosive liquid holding tank. It is equipped with a cover 101 on the top, a first liquid inlet system 102 connected to the upper side, and a first reflux system 103 connected to the lower side.

[0037] Tank 2 is a reaction vessel. The first liquid inlet system 102 and the first reflux system 103 are both connected to one side of Tank 2. A cover 201 is provided on the outer side of the top of Tank 2, and a temperature display is provided on the cover 201. A temperature sensor 202 is provided on the inner side of the top of Tank 2, and the temperature sensor 202 is electrically connected to the temperature display. A sample placement plate 205 is provided at the bottom inside of Tank 2, and a heating device 203 is provided below the sample placement plate 205. The outer wall of Tank 2 is covered with an outer cooling material 204 (outer cooling and protective material for the reaction vessel).

[0038] Tank 3 is a container for saturated sodium bicarbonate neutralization solution. It is equipped with a cover 301 on the top, a second liquid inlet system 303 connected to the upper side, and a second reflux system 302 connected to the lower side. Both the second liquid inlet system 303 and the second reflux system 302 are connected to the other side of tank 2.

[0039] Tank No. 4 is a tap water inlet system, which is connected to the outer cooling material 204 to form an outer cooling system.

[0040] Tank No. 5 is a waste liquid discharge tank, which is connected to the bottom of Tank No. 2 through the waste liquid inlet system 501.

[0041] The low-magnification etching method of the present invention includes the following steps: (1) Cut a TA1 and Q235 titanium steel composite material, process the composite interface into a low magnification sample (size 10×60mm), check that the surface roughness of the observation surface has reached the requirement of 3.2μmRa(▽5), and clean the entire sample with hot laundry detergent solution to remove oil stains from the surface of the low magnification sample. (2) Prepare the following low-magnification corrosive agent for the above titanium-steel composite material: 2 parts by mass of potassium fluoride, 10 parts by volume of sulfuric acid, 8 parts by mass of oxalic acid, 5 parts by mass of formic acid, 6 parts by volume of nitric acid, 1 part by mass of di-o-toluenethiourea, 1 part by mass of sodium lauryl ether sulfate, and the remainder is distilled water. Place the prepared corrosive agent in tank 1. Prepare a saturated sodium bicarbonate aqueous solution and place it in tank 3. Prepare a cleaning agent: 5 parts by volume of nitric acid, 100 parts by volume of ethanol, and 2 drops of detergent. Store the prepared solution separately.

[0042] (3) Place the sample to be tested on the pad (sample placement pad 205), and put the corrosive liquid into the reaction tank of the second tank 2 through the first liquid inlet system 102. Start the heating device 203 and the outer cooling system to control the corrosion process within the temperature range of 30℃~45℃. After the sample to be tested is thermally eroded for 5 minutes, the corrosive liquid is returned to the first tank 1 through the first reflux system 103. (4) Start the second liquid inlet system 303 to put the neutralizing liquid into the reaction tank of the second tank 2. After the test sample is fully neutralized, start the second reflux system 302 to return the neutralizing liquid to the third tank 3. (5) Put tap water into tank 2 to rinse the test sample obtained in step (4), and the waste liquid enters tank 5. (6) Take out the sample and wipe it with the above cleaning agent to remove the surface corrosion deposits, rinse and blow dry; (7) Observe the bonding interface and the surface quality of the titanium and steel layers of the corroded low-magnification sample with the naked eye or stereomicroscope. The low-magnification morphology is shown in the figure. Figures 1-2 .

[0043] The method of this invention can accurately display low-magnification information of titanium-steel composite plates, directly measure the dimensions of the titanium and steel sides, and indirectly evaluate the flatness of the titanium and steel sides and the composite quality of the composite interface, thus playing a supporting role in the development and application of titanium-steel composite plates.

[0044] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A low-magnification corrosion method for titanium-steel composite plates, characterized in that, A low-magnification etchant for titanium-steel composite plates is used. The etchant is a mixed solution of potassium fluoride, sulfuric acid, oxalic acid, formic acid, nitric acid, di-o-toluenethiourea, sodium lauryl ether sulfate, and water. The content of potassium fluoride is 1-5 parts by mass, the content of sulfuric acid is 10-15 parts by volume, the content of oxalic acid is 5-10 parts by mass, the content of formic acid is 5-10 parts by mass, the content of nitric acid is 3-8 parts by volume, the content of di-o-toluenethiourea is 0.5-1 parts by mass, the content of sodium lauryl ether sulfate is 0.5-2 parts by mass, and the water in the solution is distilled water. The etching temperature of the low-magnification etchant on the titanium-steel composite plate for the low-magnification sample is 30~45℃, and the etching time is 2~8min. The titanium-steel composite plate material has a titanium cladding layer and a steel base layer, wherein the titanium is TA1 and the steel is Q235; The low-magnification corrosion method for the titanium-steel composite plate includes the following steps: S1. Take a section of the TA1 and Q235 titanium steel composite material, process the composite interface into a low-magnification sample, check that the surface roughness of the observation surface has reached the requirement of 3.2μmRa, and clean the entire sample with hot laundry detergent solution to remove oil stains from the surface of the low-magnification sample. S2. Prepare a low-multiplier corrosive agent for titanium-steel composite materials and place the prepared corrosive agent in tank No. 1 (1); S3. Prepare the neutralizing solution and place the prepared neutralizing solution in tank No. 3 (3); S4. Prepare the cleaning agent and store it separately after preparation. S5. Place the sample to be tested on the sample placement pad (205), and transport the corrosive agent to the second tank (2) through the first liquid inlet system (102). Start the heating device (203) and the outer cooling system to control the corrosion process within the temperature range of 30℃~45℃. After the sample to be tested is thermally eroded for 5 minutes, the corrosive agent is returned to the first tank (1) through the first reflux system (103). S6. Start the second liquid inlet system (303) to deliver the neutralizing liquid to the second tank (2). After the test sample is fully neutralized, start the second reflux system (302) to return the neutralizing liquid to the third tank (3). S7. Put tap water into tank No. 2 (2) to rinse the test sample obtained in step S6. The waste liquid after rinsing enters tank No. 5 (5). S8. Remove the sample and wipe it with a cleaning agent to remove the corrosion deposits on the sample surface. Then rinse and dry the sample. S9. Observe the bonding interface and the surface quality of the titanium and steel layers of the corroded low-magnification sample with the naked eye or stereomicroscope.

2. The low-magnification corrosion method for titanium-steel composite plates according to claim 1, characterized in that, In step S2, the low-magnification corrosive agent for titanium-steel composite materials includes: 2 parts by mass of potassium fluoride, 10 parts by volume of sulfuric acid, 8 parts by mass of oxalic acid, 5 parts by mass of formic acid, 6 parts by volume of nitric acid, 1 part by mass of di-o-toluenethiourea, 1 part by mass of sodium lauryl ether sulfate, and the remainder is water.

3. The low-magnification corrosion method for titanium-steel composite plates according to claim 1, characterized in that, In step S3, the neutralizing solution is a saturated sodium bicarbonate aqueous solution.

4. The low-magnification corrosion method for titanium-steel composite plates according to claim 1, characterized in that, In step S4, the cleaning agent includes: 3-6 parts by volume of nitric acid, 100 parts by volume of ethanol and 1-3 drops of detergent.

Citation Information

Patent Citations

  • Method for observing metallographic structure on titanium / steel explosion welding interface

    CN102072834A

  • A low-magnification inspection method for rolled titanium-steel clad plate

    CN103900959B

  • Macroscopic inspection method of rolled titanium-steel composite plate

    CN103900959A

  • Metallographic corrosion device of steel test sample

    CN108051278A

  • Hot acid corrosion steel low-power corrosion equipment and use method

    CN116087081A